Digital Marketing terhadap Keputusan Pembelian Sepatu Kanky di Shopee pada Gen-Z Garut - Diana, Didah Sadidah; Rohimat Nurhasan; Husni Muharam (Politeknik Piksi Ganesha Indonesia, 2025)
The rise of digital technology has shifted consumer buying behavior, especially among Gen-Z who are highly active on online platforms. This study aims to examine the influence of digital marketing on the purchasing decisions of Kanky shoes on Shopee among Gen-Z in Garut. A quantitative associative method was applied using SEM-PLS with SmartPLS 3, involving 100 respondents. The study focuses on digital marketing strategies such as social media, content, and promotional campaigns. Results show that digital marketing has a positive and significant effect on purchasing decisions. These findings support the theory that digital exposure shapes consumer perceptions and drives purchase decisions. The study concludes that digital marketing plays a key role in influencing Gen-Z consumer behavior. Keywords:Digital Marketing, Purchase Decision, Gen -Z